Climate change impacts to extreme weather events associated with insured losses in New Zealand: a review - Joanna Aldridge; Rob Bell (Environmental Research: Climate)
In 2023, New Zealand experienced two consecutive weather-related events that exceeded previous insured losses by more than a factor of ten: the Auckland Anniversary Day floods and ex-Tropical Cyclone Gabrielle. Further, climate reporting for financial services becomes mandatory in this jurisdiction in 2024, yet established catastrophe models are not available for a range of perils in New Zealand. Insurers hence need to better understand weather-related catastrophes in New Zealand and the impact of climate change in this island nation exposed to strong marine influences and weather events of both tropical and temperate origin. This comprehensive review seeks to integrate and interpret the findings from a wide range of scientific literature into a cohesive summary useful for insurers evaluating climate risk in New Zealand. This review summarises the climate risk facing New Zealand, focussing on extreme events including heavy rainfall, floods, coastal hazards driven by weather systems on a range of spatiotemporal scales: atmospheric rivers, ex- and extra-tropical cyclones and severe convective storms, as well as wildfire weather. Potential changes to natural climate variability are also considered. The review shows that extreme rainfall over a range of durations, but particularly shorter durations, is projected to increase, and riverine and coastal flooding will also increase, although potential impacts are less well understood. Extreme weather systems such as ex-tropical and extra-tropical cyclones may be supported by warmer sea surface temperatures and the poleward shift in subtropical weather systems, although quantitative studies on their changing frequency and severity are not yet available. Key knowledge gaps in understanding sources of extreme rainfall, ex-tropical cyclones and other low-pressure systems and severe convective storms are identified. Further, focus areas for climate-related risk reduction that insurers could seek to promote to help protect the New Zealand community are discussed.